2018
DOI: 10.3390/met8121079
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution in ODS Alloys with a High-Volume Fraction of Nano Oxides

Abstract: Existing oxide dispersion strengthened (ODS) alloys are, besides Ni-based superalloy single crystals, the most creep-resistant materials. The creep resistance of the ODS alloys may, moreover, be significantly improved thanks to increasing the volume fraction of the nano oxides by more than one order of magnitude so that the oxides play a decisive role in strengthening. The present experimental study deals with two systems of such a high-volume fraction of nano oxides, namely, the Fe-11Al-1O and Fe-17Cr-7Al-4Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 23 publications
6
29
0
Order By: Relevance
“…Excellent creep strength of the ODS alloys is associated with an attractive interaction between dislocations and nano-oxides as it is successfully modelled by Rösler and Arzt [19], who also predict a threshold stress for creep and its significant drop with coarsening of the nano-oxides. The coarsening kinetics of particles in multicomponent systems is modelled by Fisher et al [20] and experimentally studied e.g., by Bartkova et al [21] or by Svoboda et al [22] indicating a very high 2 of 13 resistance of Y-nano-oxides against coarsening in ODS alloys. The benefits of high creep resistance of ODS alloys at very high temperatures are conditioned by a sufficiently good oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excellent creep strength of the ODS alloys is associated with an attractive interaction between dislocations and nano-oxides as it is successfully modelled by Rösler and Arzt [19], who also predict a threshold stress for creep and its significant drop with coarsening of the nano-oxides. The coarsening kinetics of particles in multicomponent systems is modelled by Fisher et al [20] and experimentally studied e.g., by Bartkova et al [21] or by Svoboda et al [22] indicating a very high 2 of 13 resistance of Y-nano-oxides against coarsening in ODS alloys. The benefits of high creep resistance of ODS alloys at very high temperatures are conditioned by a sufficiently good oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The research effort of the authors resulted in development of a mechanically alloyed powder with a very high content of O, allowing production of an ODS alloy (called new-generation ODS alloy by the authors) of rather high nano-oxide volume fraction of about 5%, which exceeds the volume fraction in classical ODS alloys by one order of magnitude [4,6]. The processing of the new-generation ODS alloy consists of three steps [22]: (1) MA to produce chemically homogeneous powders, (2) hot consolidation of the powders by intensive plastic deformation, e.g., by rolling, providing a compact ultra-fine grained alloy due to an intensive dynamic recrystallization and (3) heat treatment to provoke secondary recrystallization leading to rather coarse-grained microstructure conditioning an excellent creep resistance. A complex optimization of the chemical composition of the new-generation ODS alloy performed recently by the authors of the Institute of Physics of Materials leads to conclusion that pure Y-nano-oxides as strengthening particles are much better with respect to coarsening than other nano-oxides [21,22], as well as in terms of the cohesive strength of grain boundaries being influenced by wetting of the nano-oxides (unpublished results).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was confirmed that they grow during annealing at 1200 • C. As the nano-oxides are very stable against coarsening up to temperatures of 1000 • C, and their number density is kept very high, the Zener pinning effect is also active at these temperatures. The Zener pinning effect decreases due to the coarsening of nano-oxides at temperatures over 1200 • C, and secondary recrystallization takes place [25].…”
Section: Metallographic Analysismentioning
confidence: 99%
“…As the nano-oxides are very stable against coarsening up to temperatures of 1000 °C, and their number density is kept very high, the Zener pinning effect is also active at these temperatures. The Zener pinning effect decreases due to the coarsening of nano-oxides at temperatures over 1200 °C, and secondary recrystallization takes place [25]. It is very difficult to measure the grain size with automatic software and therefore the evaluation is done by in-house software according to the American Society for Testing and Materials (ASTM) E112-13, "Standard Test Methods for Determining Average Grain Size".…”
Section: Metallographic Analysismentioning
confidence: 99%